Establishment of critical limits of indicators and indices of soil quality in rice-rice cropping systems under different soil orders - Biswas, Sunanda; Hazra, G.C.; Purakayastha, T.J.; Saha, N.; Mitran, Tarik; Singha Roy, Satadeep; Basak, Nirmalendu; Mandal, Biswapati (Geoderma, 2017)
Rice-rice is one of the major cropping systems in Indo-Gangetic Plains (IGP) of South Asia. Assessment of soil quality and identification of key indicators with their critical limits are very much important for maintaining normal functioning of the soil and productivity of crops, particularly of wet land rice. The present investigation was undertaken to identify sensitive soil quality indicators and to develop soil quality indices and establishment of their critical limits in Inceptisols, Entisols and Alfisols collected from farmers' fields with long-term rice-rice cropping system in sub-tropical India. The soil samples were analysed for 37 physical, chemical and biological properties. Principal component analysis (PCA) was performed to create minimum data set (MDS) of physical, chemical and biological indicators which were encompassed to develop unified soil quality index (SQI) under different soil orders. The SQI thus developed was highest in Inceptisols (0.66 to 0.89) followed by Entisols (0.23 to 0.76) and Alfisols (0.37 to 0.60). The upper and lower critical limits for key indicators as well as SQI were determined using scattered plot technique involving relative yields of rice (RY) and different soil quality indicators as well as SQI. The critical limit equivalent to 80% and 40% of relative yield were treated as upper and lower critical limits of selected key indicators and SQI. The adequacy classes for each of selected key indicator as a function of relative yield of rice were established based on the following criteria: <40% low, 40–80% moderate and >80% adequate. The upper and lower critical limits of the indicators selected under rice-rice cropping systems in Inceptisols were available Zn (1.7 and 1.2mgkg−1), bulk density (1.2 and 1.6Mgm−3), β-glucosidase activity (68 and 18μgp-nitrophenolg−1soilh−1) and urease activity (64 and 24μgNH4g−1soil2h−1), in Entisols were dehydrogenase activity (93 and 12μgTPFg−1soil24h−1), aggregate stability (66 and 11%), total organic C (11.6 and 10.7gkg−1) and pHw (5.7 and 5.3) and in Alfisols were oxidisable organic C (7.8 and 5.0gkg−1), β-glucosidase activity (51 and 15μgp-nitrophenolg−1soilh−1), aggregate stability (52 and 19%) and mineralizable C (273 and 173μgCg−1 soil), respectively. The upper and lower critical limits established for key soil quality indicators as well as soil quality indices for Inceptisols (0.85 and 0.56), Entisols (0.23 and 0.65) and Alfisols (0.37 and 0.56) could periodically be judged for maintaining/enhancing soil quality and yield sustainability through the employment of optimum management practices in rice-rice cropping systems of subtropical India. •Soil quality was evaluated under different soil orders in rice-rice system.•Inceptisols showed better soil quality than Entisols and Alfisols.•Soil quality indicators were identified through principal component analysis.•The critical limits of key indicators and indices of soil quality were established.